2023
DOI: 10.47197/retos.v49.98234
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la actividad física en la repetición de curso de los adolescentes de Granada (Effects of physical activity on grade repetition among adolescents in Granada)

María Rosario Salazar-Ruiz,
José Manuel Alonso-Vargas,
Félix Zurita-Ortega
et al.

Abstract: Hace décadas se tenía una percepción de cuerpo y mente de forma independiente. Sin embargo, hoy en día son percibidas como un conjunto, ya que ha quedado demostrado que el ejercicio físico tiene consecuencias a nivel cognitivo. Por esta razón, en esta investigación se propone conocer la relación que existe entre la realización o no de ejercicio físico con la repetición de uno o más cursos en adolescentes. Para ello, se ha utilizado una muestra de un total de 706 adolescentes de institutos pertenecientes a la p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Jogging is said to be an aerobic exercise if it is done for a long time, and the intensity of the exercise ranges from 70-85% of the maximum pulse (Khundam & Nöel, 2021). Jogging is a sport that can be done to maintain health (Salazar-Ruiz et al, 2023). From some of the definitions above, it can be concluded that jogging is a sport that is included in the type of aerobic exercise where the activities carried out are useful for improving body health, especially physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Jogging is said to be an aerobic exercise if it is done for a long time, and the intensity of the exercise ranges from 70-85% of the maximum pulse (Khundam & Nöel, 2021). Jogging is a sport that can be done to maintain health (Salazar-Ruiz et al, 2023). From some of the definitions above, it can be concluded that jogging is a sport that is included in the type of aerobic exercise where the activities carried out are useful for improving body health, especially physical fitness.…”
Section: Introductionmentioning
confidence: 99%